States and regions in the European Union : institutional adaptation in Germany and Spain - Börzel, Tanja A., 1970- (Cambridge, UK ; New York : Cambridge University Press, 2002)
"Tanja Borzel argues that the effect of Europeanization on the politics and institutions of the EU's member states depends on the degree of conflict between European and domestic norms and rules. The book examines the relationship between the central state and regions in Germany and Spain, showing how Europeanization has served to weaken the powers of the regions. In both countries, the regions were forced to cooperate more closely with the centre, but the institutional impact in the two countries has been strikingly different. In Germany the existing cooperative Federal system was reinforced, but in Spain the traditional competitive relationship between the levels of government could not continue.
Europeanization has led to a significant change in the pattern of Spanish politics, turning rivalry into cooperation. This book thus presents an important analysis of the impact of Europeanization on domestic politics, and on the relationship between states and regions in particular."--Jacket
Europeanization and domestic institutional change : a historical institutionalist approach -- Reinforcing cooperative federalism : institutional adaption to Europeanization in Germany -- Transforming competitive regionalism : institutional adaptation to Europeanization in Spain -- Sharing versus shifting the costs of adaptation : the Europeanization of environmental policy-making in Germany and Spain.
Includes bibliographical references (pages 240-264) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: European Union; European Union; Union européenne -- Allemagne; Union européenne -- Espagne; Federal government -- Germany; Central-local government relations -- Germany; Federal government -- Spain; Central-local government relations -- Spain; Germany -- Politics and government -- 1990-; Spain -- Politics and government -- 1982-; Relations gouvernement central-collectivités locales -- Allemagne; Relations gouvernement central-collectivités locales -- Espagne; POLITICAL SCIENCE -- Civics & Citizenship; Central-local government relations; Federal government; Politics and government; Germany; Spain; Europäisierung; Spanien; Deutschland; Federaal bestuur; Regionaal bestuur; Europese integratie; Gouvernement fédéral -- Espagne; Relations gouvernement central-collectivités locales -- Espagne; Gouvernement fédéral -- Allemagne; Relations gouvernement central-collectivités locales -- Allemagne; Europäische Union; Since 1982; Electronic book; Electronic books